Accumulation of nodularin in New Zealand shortfin eel (Anguilla australis): potential consequences for human consumption. Issue 3 (3rd July 2017) - Dolamore, B; Puddick, J; Wood, SA
ABSTRACT: The native Anguilla australis (shortfin eel) is a culturally significant species for indigenous Māori populations of New Zealand. At Lake Forsyth/Te Wairewa (Canterbury), local Māori have depended on A. australis as a source of mahinga kai (traditional food) for centuries. This lake experiences blooms of Nodularia spumigena and the associated hepatotoxin nodularin has been detected in water samples. This study aimed to determine if nodularin accumulated in A. australis, and whether levels posed a health risk for human consumption. The maximum concentrations of N. spumigena and nodularin detected in lake water samples were 240 × 10 6 cells/mL and 91, 000 µg/L, respectively. Nodularin was detected in the liver and muscle of eels (max. 147 µg/kg in liver and 29 µg/kg in muscle). One muscle sample exceeded the recommended levels for safe human consumption of nodularin in fish (24 μg/kg).